Characterization and Safety Assessment of a Novel Antioxidant Excipient from Sustainable Recovery of Grape Processing Waste Bentonite Designed to Develop a Thermosensitive Buccal Spray for Oral Cavity Wellness - Giulia Di Prima; Elena Belfiore; Cecilia La Mantia; Serena Indelicato; Giuseppe Avellone; Viviana De Caro (Pharmaceutics)
Background/Objectives: Nowadays, sustainability efforts focus on extracting natural cosmeceutical ingredients, such as polyphenols, from agri-food waste, for example, black bentonite (BB). The aims of this work were to validate an antioxidant cosmetic ingredient obtained from the waste BB and embed it into an ad hoc designed oromucosal spray intended for oral cavity wellness. Methods: Focusing on sustainability, the study tested PEG200, propylene glycol, and their mixtures as unconventional and green extraction solvents, aligned with a waste-to-market approach. The extracts obtained by maceration were characterized through HPLC-DAD and HPLC-MS analyses, DPPH, Bradford, and Folin–Ciocalteu assays. The best P extract was further subjected to OECD-compliant in vitro validation as novel cosmetic raw material and used to prepare a thermosensitive buccal spray for oral daily care. Results: PEG200 enabled the obtainment of a cost-effective polyphenol-rich extract, which was validated as a safe, high value-added cosmetic secondary raw material. The extract was incorporated into a liquid thermosensitive buccal formulation, able to gel once at body temperature and enhance polyphenol accumulation into the oral mucosae even with short contact times. Conclusions: BB is confirmed as a valuable source of polyphenols, and PEG200 represents an effective extraction solvent leading to a novel functional liquid excipient characterized by an OECD-compliant variegate pool of phenols. The buccal spray then proposed represents a valuable, friendly solution for daily oral care, as it is simple to use, as well as the in vitro and ex vivo tests carried out suggested its effectiveness.